Determination of optimum polymeric coagulant in palm oil mill effluent coagulation using multiple-objective optimisation on the basis of ratio analysis (MOORA) - Tamrin, Khairul Fikri; Zahrim, A.Y. (Springer Verlag, 2017)
The main limitation of a conventional palm oil mill effluent (POME) ponding system lies in its inability to completely decolourise effluent. Decolourisation of effluent is aesthetically and environmentally crucial. However, determination of the optimum process parameters is becoming more complex with the increase of the number of coagulants and responses. The primary objective of this study is to determine the optimum polymeric coagulant in the coagulation–flocculation process of palm oil mill effluent by considering all output responses, namely lignin–tannin, low molecular mass coloured compounds (LMMCC), chemical oxygen demand (COD), ammonia nitrogen (NH3-N), pH and conductivity. Here, multiple-objective optimisation on the basis of ratio analysis (MOORA) is employed to discretely measure multiple response characteristics of five different types of coagulants as a function of assessment value. The optimum coagulant is determined based on the highest assessment value and was identified as QF25610 (cationic polyacrylamide). On the other hand, the lowest assessment value was represented by AN1800 (anionic polyacrylamide). This study highlights the simplicity of MOORA approach in handling various input and output parameters, and it may be useful in other wastewater treatment processes as well.